Incapacitation: Revisiting an Old Question with a New Method and New Data - Sweeten, Gary (Journal of quantitative criminology, 2007)
We use the National Longitudinal Survey of Youth 1997 to obtain estimates of the number of crimes avoided through incapacitation of individual offenders. Incarcerated individuals are matched to comparable non-incarcerated counterparts using propensity score matching. Propensity scores for incarceration are calculated using a wide variety of time-stable and time-varying confounding variables. We separately analyze juvenile (age 16 or 17) and adult (age 18 or 19) incapacitation effects. Our best estimate is that between 6.2 and 14.1 offenses are prevented per year of juvenile incarceration, and 4.9 to 8.4 offenses are prevented per year of adult incarceration.